Intestinal Amyloidosis in common variable immunodeficiency and Rheumatoid Arthritis - Meira, T.; Sousa, R.; Cordeiro, A.; Ilgenfritz, R.; Borralho, P. (Hindawi Publishing Corporation, 2015)
We present a case of reactive amyloidosis that developed secondary to common variable immunodeficiency and rheumatoid arthritis. A 66-year-old woman, with prior history of common variable immunodeficiency and rheumatoid arthritis, was referred to our clinic for chronic diarrhea investigation. The patient was submitted to colonoscopy with ileoscopy, which did not show relevant endoscopic alterations. However, undertaken biopsies revealed amyloid deposition. Since amyloidosis with GI involvement is a rare cause of chronic diarrhea, this pathology should be considered in etiologic investigation, especially when associated with chronic inflammatory diseases.
Keywords: Intestinal Amyloidosis; Rheumatoid Arthritis; Immunodeficiency